PERANAN PEMUDA SIMALUNGUN DALAM MEMPERTAHANKAN KEMERDEKAAN REPUBLIK INDONESIA 1945-1946 - hanafiah; Purba, Monica Sondang Arianta (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
As for the results of this study, it is when Japan enters the simalungun people's warm welcome to Japan's arrival because Japan has been able to beat down the Dutch but since Japan fully ruled the people's lives and young men have continued to suffer because at the time of Japan's rule there was an infusion of romusha for healthy young men and girls. This is the basis for the development of the young cynic movement. They also made good use of the Japanese military training for an independent campaign, and a huge contribution was made by the young men of the sloungun to form the fighting ranks, during the blood and blood of the hotel, to revolutionize in the simalungun